2002
DOI: 10.3354/meps240027
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of sedimentary metals from a contaminated bay

Abstract: Sediments are considered the sink for metals in aquatic environments because of their strong metal-binding capacity, but they are a potential source for metal ingestion by marine benthic animals as well. Sediment contamination is now a major environmental problem in many countries, including China. This study examines the bioavailability to a marine suspension-feeder (the clam Mactra veneriformis) and a deposit-feeder (the peanut worm Sipunculus nudus) of sediment-bound Cd, Cr and Zn along a gradient of metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 33 publications
5
33
1
1
Order By: Relevance
“…Experimental data and kinetic modeling have shown that the passage of sediment through the digestive tract determines heavy metal accumulation by deposit-feeding polychaetes and sipunculans [22,31,32]. Comparison of the trace element composition of organisms from polluted and relatively clean areas has revealed a relation between metal storage by infauna and the environmental concentrations of metals.…”
Section: Resultsmentioning
confidence: 97%
“…Experimental data and kinetic modeling have shown that the passage of sediment through the digestive tract determines heavy metal accumulation by deposit-feeding polychaetes and sipunculans [22,31,32]. Comparison of the trace element composition of organisms from polluted and relatively clean areas has revealed a relation between metal storage by infauna and the environmental concentrations of metals.…”
Section: Resultsmentioning
confidence: 97%
“…Chen and Mayer, 1999;Ahrens et al, 2001a). Further, several studies suggest that animal taxon and physiology are important controls on faunal feeding and digestive processes (Mayer et al, 1996;Wang et al, 2002). Different taxa have been shown to ingest different particle sizes, and to assimilate compounds from different food sources with varying efficiency .…”
Section: Introductionmentioning
confidence: 97%
“…This, possibly, explains the absence of any significant spatial variations in metal concentrations between the two sampling sites. The results possibly suggest that the levels of contamination of these metals do not exceed the clam's capacity of regulation (Wang et al 2002).…”
Section: Discussionmentioning
confidence: 97%